Stress of endoplasmic reticulum modulates differentiation and lipogenesis of human adipocytes - Koc, Michal; Mayerová, Veronika; Kračmerová, Jana; Mairal, Aline; Mališová, Lucia; Štich, Vladimír; Langin, Dominique; Rossmeislová, Lenka (Biochemical and biophysical research communications, 2015)
BACKGROUND: Adipocytes are cells specialized for storage of neutral lipids. This storage capacity is dependent on lipogenesis and is diminished in obesity. The reason for the decline in lipogenic activity of adipocytes in obesity remains unknown. Recent data show that lipogenesis in liver is regulated by pathways initiated by endoplasmic reticulum stress (ERS). Thus, we aimed at investigating the effect of ERS on lipogenesis in adipose cells. METHODS: Preadipocytes were isolated from subcutaneous abdominal adipose tissue from obese volunteers and in vitro differentiated into adipocytes. ERS was induced pharmacologically by thapsigargin (TG) or tunicamycin (TM). Activation of Unfolded Protein Response pathway (UPR) was monitored on the level of eIF2α phosphorylation and mRNA expression of downstream targets of UPR sensors. Adipogenic and lipogenic capacity was evaluated by Oil Red O staining, measurement of incorporation of radio-labelled glucose or acetic acid into lipids and mRNA analysis of adipogenic/lipogenic markers. RESULTS: Exposition of adipocytes to high doses of TG (100 nM) and TM (1 μg/ml) for 1-24 h enhanced expression of several UPR markers (HSPA5, EDEM1, ATF4, XBP1s) and phosphorylation of eIF2α. This acute ERS substantially inhibited expression of lipogenic genes (DGAT2, FASN, SCD1) and glucose incorporation into lipids. Moreover, chronic exposure of preadipocytes to low dose of TG (2.5 nM) during the early phases of adipogenic conversion of preadipocytes impaired both, lipogenesis and adipogenesis. On the other hand, chronic low ERS had no apparent effect on lipogenesis in mature adipocytes. CONCLUSIONS: Acute ERS weakened a capacity of mature adipocytes to store lipids and chronic ERS diminished adipogenic potential of preadipocytes.
Keywords: Tunicamycin; Adipocytes; tunikamycin; Humans; Cell Differentiation; fosforylace; fyziologický stres; Lipids; lipidy; tukové buňky; endoplazmatické retikulum; signální dráha UPR; Phosphorylation; Stress, Physiological; thapsigargin; Thapsigargin; lidé; buněčná diferenciace; Unfolded Protein Response; Endoplasmic Reticulum